Survei Pengaruh Erupsi Gunung Sinabung terhadap Penyakit Hawar Daun (Phytophthora infestans) pada Tanaman Kentang (Solanum tuberosum Linn.) di Kecamatan Simpang Empat - Febepriskila Br Tarigan; Yuswani Pangestiningasih; Lahmuddin Lubis (Universitas Sumatera Utara, 2015)
The aim of experiment was to find out the effect of mount Sinabung on leaf blight disease(Phytophthora infestans) disease on potatoes (Solanum tuberosum Linn.). The research was held atSimpang Empat districts, Karo distric, North Sumatera from March until May 2014. This researchwas conducted using survey method by simple linear regression quantitative analyzis, ie regressionof the number of eruption regression and incidence of leaf blight disease percentage, regressionbetween the control after occurres eruption with incidence of leaf blight disease and regression leafblight disease between control after occurres eruption with production of potatoes. The resultshowed that the number of eruption did have significant relationship with incidence of leaf blightdisease percentage, and the control after occurance of the eruption did have significant relation withincidence of disease and production of potatoes in Simpang Empat distric. The highest incidence ofdisease in Torong village with 1.6% and the lowest were showed in Bilan Baru village with 1.1%.The highest potatoes production was in Bulan Baru village with 9.4 Ton/Ha and the lowestproduction was in Ujung village with 5.4 Ton/Ha.Keywords : potatoes, leaf blight disease and Sinabung eruption